IL-1 Inhibitors in the Treatment of Familial Mediterranean Fever: Treatment Indications and Clinical Features in a Large Real-World Cohort - Yalcin-Mutlu, Melek; Icacan, Ozan Cemal; Yildirim, Fatih; Temiz, Selahattin Alp; Fagni, Filippo; Schett, Georg; Tascilar, Koray; Minopoulou, Ioanna; Burul, Gokhan; Bes, Cemal (Journal of Clinical Medicine, 2024)
Background: The accruing evidence about the efficacy of anti-IL-1 agents in Familial Mediterranean Fever (FMF) patients led to their widespread off-label use. Therefore, identifying precise indications and clinical characteristics of IL-1i-warranting patients are important. This study investigated the clinical characteristics and treatment indications of patients with FMF requiring interleukin 1 inhibition therapy (IL-1i). Methods: Hospital records of FMF patients attending a tertiary care center at the Department of Rheumatology, University of Health Sciences, Basaksehir Cam and Sakura City Hospital were retrospectively analyzed. Data on symptoms and disease manifestations, age of symptom onset, time to diagnosis, MEFV variants, type of treatment, and their indications were collected. Results: Between June 2020 and March 2023, 312 FMF patients were identified. The mean age at the onset of symptoms was 14.0, and the mean time to diagnosis was 11.9 years. In total, 87.1% of patients were receiving colchicine monotherapy, while the remaining 11.8% warranted IL-1i. Clinical symptoms and flare manifestations did not show a significant difference between the two groups. However, patients receiving IL-1i started having symptoms at younger age (11.5 vs. 14.5, p = 0.042) and time to diagnosis was longer (18.2 vs. 11.0, p < 0.01). M694V homozygosity was more common in patients receiving IL-1i. Indications for patients receiving IL-1i were colchicine resistance (8.0%), secondary amyloidosis (5.1%), and colchicine intolerance (2.2%). Conclusions: This study shows that a subset of FMF patients, particularly those with a more severe phenotype with an earlier disease onset and M694V homozygosity, require IL-1i treatment despite the overall good efficacy and tolerability of colchicine, primarily due to colchicine resistance, intolerance, or complications such as amyloidosis.
CRIS-Team Scopus Importer:2024-07-12
Keywords: amyloidosis; colchicine intolerance; colchicine resistance; familial mediterranean fever; interleukin-1 inhibitors